Expression of kidney injury molecule-1 (Kim-1) in relation to necrosis and apoptosis during the early stages of Cd-induced proximal tubule injury - Prozialeck, Walter C. (2009)
Cadmium (Cd) is a nephrotoxic industrial and environmental pollutant that causes a generalized dysfunction of the proximal tubule. Kim-1 is a transmembrane glycoprotein that is normally not detectable in non-injured kidney, but is up-regulated and shed into the urine during the early stages of Cd-induced proximal tubule injury. The objective of the present study was to examine the relationship between the Cd-induced increase in Kim-1 expression and the onset of necrotic and apoptotic cell death in the proximal tubule. Adult male Sprague-Dawley rats were treated with 0.6 mg (5.36 μmoles) Cd/kg, subcutaneously, 5 days per week for up to 12 weeks. Urine samples were analyzed for levels of Kim-1 and the enzymatic markers of cell death, lactate dehydrogenase (LDH) and alpha-glutathione-S-transferase (α-GST). In addition, necrotic cells were specifically labeled by perfusing the kidneys in situ with ethidium homodimer using a procedure that has been recently developed and validated in the Prozialeck laboratory. Cryosections of the kidneys were also processed for the immunofluorescent visualization of Kim-1 and the identification of apoptotic cells by TUNEL labeling. Results showed that significant levels of Kim-1 began to appear in the urine after 6 weeks of Cd treatment, whereas the levels of total protein, α-GST and LDH were not increased until 8–12 weeks. Results of immunofluorescence labeling studies showed that after 6 weeks and 12 weeks, Kim-1 was expressed in the epithelial cells of the proximal tubule, but that there was no increase in the number of necrotic cells, and only a modest increase in the number of apoptotic cells at 12 weeks. These results indicate that the Cd-induced increase in Kim-1 expression occurs before the onset of necrosis and at a point where there is only a modest level of apoptosis in the proximal tubule.